Different bodies: Normality and embodiments of disability and gender - Ganterer, Julia (Sodobna pedagogika, 2019)
This article is devoted to the challenge of human diversity being perceived as difference, eventually resulting in othering and social oppression. We introduce Luan, a young disabled woman, and her gendered disabling experience in terms of embodiment, which we argue is a form of socially situated knowledge. Our intention is to shed light on a society-critical approach to gender and disability in order to counter recent developments in educational studies towards individualisation and away from socialisation as a central pedagogical moment. Luan's experience is presented in a phenomenological reading to gain an understanding of embodiments of normality and difference and to simultaneously question how far they emerge from external oppression and/or internalised desires of conforming to social norms. We conclude that for a critical and empowering pedagogy of gender and disability, both individual and societal factors have to be taken into consideration, and we accordingly introduce pedagogical perspectives of empowerment.
Keywords: disability; embodiment; fenomenologija; gender; nezmožnost; pedagogika; pedagogy; phenomenology; spol; utelešenje